EOLinPLACE - Namukwaya, Elizabeth (2024)
Funding Information: The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: The research project \u2018EOLinPLACE: Choice of where we die: a classification reform to discern diversity in individual end of life pathways\u2019 has received funding from the European Research Council (ERC) under the European Union\u2019s Horizon 2020 research and innovation programme (grant agreement no. 948609). Publisher Copyright: © The Author(s), 2024.